VAAs as sources of volatility and fragmentation: self-selection effects and genuine effects. Issue 1 (2nd January 2017) - Kleinnijenhuis, Jan; van de Pol, Jasper; van Hoof, Anita; Krouwel, André
ABSTRACT: Recent studies show that using Voting Advice Applications (VAAs) affects party preferences of voters, and hence leads to party switching. Party switching is a necessary but insufficient condition for volatility (a net switch of voters to other parties) and fragmentation (more parties gaining seats) at the aggregate level of electoral constituencies. The research question addressed here is whether the availability of VAAs in electoral constituencies weakens or strengthens trends towards greater volatility and fragmentation as observed in western democracies in the last decades. The data come from 380 Dutch municipalities during the 2014 Dutch municipal council elections. In 133 of them a VAA was available. Using a moderated mediation model that controls for the municipal self-selection of a VAA, we find that a VAA by itself leads to higher levels of volatility and fragmentation. However, VAA availability has a dampening effect in municipal constituencies with characteristics (e.g. population size, ethnic diversity, young average age) that would otherwise make them more susceptible and prone to volatility and fragmentation.